Apolipoprotein Mimetic Peptides: A New Approach for the Treatment of Asthma - Yao, Xianglan; Vitek, Michael P.; Remaley, Alan T.; Levine, Stewart J. (Frontiers in Pharmacology, 2012)
New treatments are needed for severe asthmatics to improve disease control and avoid severe toxicities associated with oral corticosteroids. We have used a murine model of house dust mite (HDM)-induced asthma to identify steroid-unresponsive genes that might represent targets for new therapeutic approaches for severe asthma. This strategy identified apolipoprotein E as a steroid-unresponsive gene with increased mRNA expression in the lungs of HDM-challenged mice. Furthermore, apolipoprotein E functioned as an endogenous negative regulator of airway hyperreactivity and goblet cell hyperplasia in experimental HDM-induced asthma. The ability of apolipoprotein E, which is expressed by lung macrophages, to attenuate AHR and goblet cell hyperplasia is mediated by low density lipoprotein (LDL) receptors expressed by airway epithelial cells. Consistent with this, administration of an apolipoprotein E mimetic peptide, corresponding to amino acids 130 to 149 of the LDL receptor-binding domain of the holo-apoE protein, significantly reduced AHR and goblet cell hyperplasia in HDM-challenged apoE-/- mice. These findings identified the apolipoprotein E - LDL receptor pathway as a new druggable target for asthma that can be activated by administration of apoE mimetic peptides. Similarly, apolipoprotein A-I may have therapeutic potential in asthma based upon its anti-inflammatory, anti-oxidative and anti-fibrotic properties. Furthermore, administration of apolipoprotein A-I mimetic peptides has attenuated airway inflammation, airway remodeling and airway hyperreactivity in murine models of experimental asthma. Thus, site-directed delivery of inhaled apolipoprotein E or apolipoprotein A-I mimetic peptides may represent novel treatment approaches that can be developed for asthma, including severe disease.